A healthy lifestyle in the system of formation of health preschool children - Nadiia Trush (Vasyl Stefanyk Precarpathian National University, 2017)
The article discusses the influence of human lifestyle on his health and well-being. The basis of healthy lifestyle among preschoolers will be the knowledge about the structure of the body, the means of preserving and strengthening human health, the necessity of careful attitude to their own health. Key words: health, healthy lifestyle, preschool age, culture, health.